Avaliação do processo de biossorção de metais pesados utilizando a macrófita Egeria densa - Santos, Gustavo Henrique Fidelis dos (2016)
The purpose of this study was to evaluate the cadmium and zinc biosorption by macrophyte Egeria densa and identify the main physical-chemical interactions and biosorption mechanisms involved in the capture of these heavy metals. Experimental tests were performed in batch system for evaluation of kinetics, equilibrium and biosorption mechanisms at different temperatures from mixing 50 mL of mono and bi-component cadium and zinc solution with 0.3 g of biomass in natura and chemically pre-treated with different reagents (acids, bases and salts) and different modes of operation (batch system and fixed bed column). Experiments of biosorption of cadium and zinc at concentrations of 0.5 mequiv L-1 and pH 5.0 were also performed in a fixed bed column using biomass in natura and chemically pre-treated at a temperature of 30ºC and volumetric flow 2.4 and 6 cm³ min-1. At all temperatures investigated (30, 40 e 50 ºC), the equilibrium biosorption time was approximately 15 minutes, but the concenctration of ions removed was higher at 30 ºC. Weber-Mortis model fitted to kinetic data, which indicated that mono and bi-component biosorption of cadmium and zinc is controled by intraparticle diffusion. In the evaluated temperature, Langmuir isotherm fitted to equilibrium data, with higher maximum removal capacity for cadmium (1.05 mequiv g-1) and zinc (1.17 mequiv g-1) at 30 ºC. The thermodynamic analysis proved that cadmium and zinc biosorption is a spontaneous, favorable, exothermic, reversible and chemisorption process. Fourier transform Infrared (FTIR) spectra of biomass before and after the biosorption showed that the surface of the biosorbent has functional groups like hydroxyl, carboxyl, amide and phosphate that were responsable to the metalic ions caputre through electrostatic interactions. Thus, it was found that the main biosorption mechanism of Cd2+/CdCl+ e Zn2+ ions was the ion exchange with Ca2+ > Mn2+ > K+ > Na+ bonded to functional groups of the biomass. The cadmium and zinc desorption with CaCl2 eluent solution recovered the Cd2+/CdCl+ and Zn2+ ions because the ion exchange is the predominant biosorption mechanism. Chemical modifications of biomass with different reagents were invistigated in order to increase the removal capacity of metal ions. Pretreatments combined with H3PO4 + NaCl solution and with CaCl2 solution increased the rate of removal of Egeria densa in approximately 19% for cadmium and 25% for zinc, as they increased the amount of exchanger ions (Na+ and Ca2+) connected to the functional groups, favoring the ion exchange mechanism. Cadmium and zinc biosorption in fixed bed column using pre-treated biomass with CaCl2 solution increased the biosorption capacity and reduced the mass transfer zone of the bed. These results indicated that the Egeria densa biomass behaves as an ion exchanger to remove metal ions and its adsorptive properties can be increased with chemical pre-treatments that favor the ion exchange mechanism.